2016
DOI: 10.3762/bjoc.12.127
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic chiral iminium and palladium catalysis: Highly regio- and enantioselective [3 + 2] annulation reaction of 2-vinylcyclopropanes with enals

Abstract: SummaryA cooperative catalytic strategy of chiral iminium catalysis by regioselective activation of the C=C bond in enals and a transition metal promoting to open the 2-vinylcyclopropanes for highly regio- and enantioselective [3 + 2] cycloaddition reaction of 2-vinylcyclopropanes with α,β-unsaturated aldehydes has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 94 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Employing a closely related catalytic system, a similar transformation was reported by Wang and co-workers using diester-substituted VCPs . In these two first examples, addition of diphosphine ligands led to an improved yield and diastereoselectivity.…”
Section: Vinylcyclopropanesmentioning
confidence: 59%
See 1 more Smart Citation
“…Employing a closely related catalytic system, a similar transformation was reported by Wang and co-workers using diester-substituted VCPs . In these two first examples, addition of diphosphine ligands led to an improved yield and diastereoselectivity.…”
Section: Vinylcyclopropanesmentioning
confidence: 59%
“…Employing a closely related catalytic system, a similar transformation was reported by Wang and co-workers using diester-substituted VCPs. 115 In these two first examples, addition of diphosphine ligands led to an improved yield and diastereoselectivity. In contrast, Rios and co-workers showed that employing diketo-substituted VCP 256 did not require any ligand on the palladium to deliver cyclopentanes such as 337−340 in good yields and enantioselectivities (Scheme 63A).…”
Section: (3 + 2) Annulationsmentioning
confidence: 95%
“…Lately several groups have reported several synergistic cycloadditions for the formation of bicyclic and spiro products. Michelet, 5 Jørgensen, 6 Wei Wang 7 and Rios 8 reported a formal ring expansion of vinyl cyclopropanes with enals for the formation of spiro compounds under Pd(0) and secondary amine catalysis. Later on, Jørgensen reported vinyl aziridine opening 9 and [4 + 2] decarboxylation 10 ( Scheme 1 top) using a synergistic approach with excellent results.…”
Section: Introductionmentioning
confidence: 99%
“…[20] A range of variants have since been developed, with nitroolefins, α,β-unsaturated keto esters and imines, activated indoles and benzofurans, and unsubstituted acrylic esters used as Michael acceptors, with the use of simple α,β-unsaturated esters currently representing a widely accepted limitation. [21] VCPs have also been employed in a dual catalytic setting as showcased by the independent reports from Vitale, [22] Jørgensen, [23] Wang [24] and Rios, [25] detailing the cooperative use of palladium and secondary amine catalysts to facilitate VCP ring opening and formal (3+2) cycloaddition with enals (Figure 1B), with the chiral organocatalyst (S)-1 responsible for enantioinduction. A range of related enantioselective processes have since been developed.…”
Section: Introductionmentioning
confidence: 99%